Predictive Role of IL-2R and IL-10 in the Anti-inflammatory Response and Antiplatelet Therapy of Kawasaki Disease: A Retrospective Study - Chun Zhang; Lun Chen; Sun Chen; Yan Bian; Jia Shen; Peng Zhang; JiaNi Song (Mediators of Inflammation)
To date, Kawasaki disease (KD) has only been able to be diagnosed and evaluated using clinical characteristics. Additionally, the therapeutic effect and cardiovascular complications could not be verified until its occurrence. The present retrospective study analyzed the dynamic alterations of inflammatory cytokines, platelet (PLT) count, and subgroups of lymphocytes, such as cluster of differentiation (CD) 8+ T cells and CD19+ B cells, under different conditions in 64 children with KD. The percentage distribution of lymphocyte subgroups and the altered neutrophil lymphocyte ratio demonstrated that the inflammatory response was dominated by the B cell-mediated humoral immune response before intravenous immunoglobulin (IVIG) treatment, but mainly by T cells via cellular cytotoxic effects after IVIG treatment. Among the different types of inflammatory cytokines, the results of the present study revealed that the altered levels of interleukin-2 receptor (IL-2R) and interleukin-10 (IL-10) were closely associated with the percentage of CD8+ T cells and CD19+ B cells. Additionally, the two cytokines exhibited more sensitive fluctuations based on the status of the children with KD in various circumstances compared with other indexes, such as the percentages of CD8+ T cells and CD19+ B cells or the PLT count. These results suggested that children with KD who are ≥4 years old may benefit from IVIG but will not benefit from decreased platelet activation or suffer less cardiovascular complications. Additionally, starting clopidogrel usage earlier as an antiplatelet strategy should be considered based on the observed continuous rise in the PLT count in children with KD receiving IVIG. In conclusion, dynamically monitoring the levels of IL-2R and IL-10 has the potential to provide indications of the intensity and development of the inflammatory response in children with KD and may contribute to the early prediction and adjustment of pathological and pharmacological effects of therapy.